Document : TECHSTYLE Series 1.0 - Jeffries, Janis (Hong Kong : Centre for Heritage, Arts and Textile, 2017)
Birnbaum, Dara ; Fei, Cao ; Ji Hye, Yeom ; Kook, Vvzela ; Maclean, Rachel ; Nisic, Natacha ; Sputniko ! ; Havelock Stevens, Tina ; Wong, Magdalena
Capturing the essence of the inaugural TECHSTYLE Series 1.0: Ariadne’s Thread, the book consists of two parts, 1.1 Video Art Exhibition and 1.2 Discussion Forum.
boek
Keywords: Sputniko!